Prevalence, predictors, and association of probable non-specific psychological distress and depression with HIV viral load among postpartum women in Cape Town, South Africa - Arendse, Gwendoline (Department of Public Health and Family Medicine, 2023)
Background: Psychological distress and depressive symptoms are prevalent among postpartum women living with HIV and may affect engagement in HIV care. We examined the prevalence and predictors of probable non-specific psychological distress and depressive symptoms and their association with elevated viral load (VL) in Cape Town, South Africa. Methods: This was a secondary analysis of data from the Postpartum Adherence Clubs for Antiretroviral Therapy trial which enrolled women who were initiated on antiretroviral therapy during the index pregnancy, had a VL 1000 copies/mL) through 24 months postpartum. Results: Among 401 women, 8% and 5% had elevated levels of psychological distress and depression, respectively. After adjusting for socio-demographic, obstetric, maternal, and HIV-related covariates, completion of some high school (adjusted odds ratio [aOR] 0.06; 95% confidence interval [CI] 0.01–0.55) and multiple infant delivery (aOR 12.82; 95% CI 1.25–127.11) were associated with elevated levels of psychological distress. Depressive symptoms were not associated with any of the covariates in an adjusted model. Neither psychological distress nor depressive symptoms were independently associated with viraemia at 24 months postpartum in a multivariable model. There were no significant differences between women with and without mental health-related outcomes in the time to elevated VL through 24 months postpartum. Conclusion: Non-specific psychological distress and depression remain prevalent among postpartum women living with HIV. Further research should explore the longitudinal effect of mental health-related outcomes and VL and interventions should be implemented to improve mental health-related problems in this population.